Analysis of Multinomial Logistics Regression on the Students Faith Data - Mutijah; Rohmad; Kholid Mawardi; Suparjo; Muhamad Slamet Yahya; Ifada Novikasari (Enthusiastic : International Journal of Applied Statistics and Data Science, 2025)
It is essential for the prospective teacher students of Islamic education to have a high faith level because it will influence their behavior. In addition, it positively impacts their social life. The level of a person’s faith will have a different impact; hence, it needs to be measured. The faith concepts and their measurement have been widely developed recently. One of them is a faith concept, which is built by two dimensions or variables, i.e., belief and behavior or feeling. Both variables can fluctuate between very high, high, moderate, low, or very low, each influencing faith. Students who study in an Islamic Religious Education study program and at the same time attend Islamic boarding school are predicted to have high faith. This paper aims to describe the level of student faith and find a suitable multinomial logistic regression model through analysis of its method. Data was collected using questionnaires filled out by 52 students. The results showed that the percentage of students’ faith levels with very high level was 5.8%, high was 36.5%, moderate was 38.5%, low was 13.5%, and very low was 5.8%. Meanwhile, the model accuracy was 94.2%.